Hakikat dan Tujuan Sanksi Pidana Islam - Nor Harika; Dina Safitri; Nina Nirmalasari; Surya Sukti (Politika Progresif : Jurnal Hukum, Politik dan Humaniora, 2024)
Islamic criminal or Fiqh Jinayah regulates criminal activities carried out by Mukhallaf. This act is classified as a criminal act because it disturbs the public and violates the rules of the Koran and Hadith.The aim is to enforce Islamic law for the benefit of the people. This crime is called jarimah and is punished with ukubah. Jarimah is divided into Hudud, Kishash, and Ta'zir. The difference in types of jarimah lies in the rights permitted. Hudud violates Allah's rights and Kishash violates individual rights. Ta'jil is a mixture of both. An example of Jarimah Kishash and Diyat is murder.